Design in Small and Medium-Sized Businesses as a Condition for Innovation, Infrastructure, and Sustainable Development in Latin America: The Case of Chile - Muñoz-Villagran, C (Common Ground Research Networks, 2022)
In Latin America, firms of all sizes are less innovative and prone to risk than their counterparts in other regions. This is especially harmful for Small and Medium Businesses (SMBs), which face the paradox of not having the resources to innovate, and, at the same time, they may not be able to keep competing unless they introduce some degree of innovation to their market offerings. In light of this, the following article proposes the use of design as discipline that can be configured as a fundamental driver of the conditions needed for innovation by working as an articulating agent between all the areas of business development within SMBs, particularly in limited-resource settings such as Latin America. This is done by establishing both design as an innovation driver in an entrepreneurial context, and the role of the designer as an innovation champion within a SMB. The article presents a cultural contextualization of Latin American innovation and entrepreneurship, followed by a brief historical and cultural investigation of the rise of the SMBs in Chile, probably the country in the region with the most advances in this area, to then use it as a starting point to devise and apply this novel approach. Later, in order to understand the dynamics of these businesses, the operating factors of the business venture ecosystem and its actors are analyzed, as well as the innovations that facilitate productivity; the infrastructures that make possible the access to commerce and distribution of products and services; and the improvements for sustainable development. The article concludes by establishing recommendations and conditions for this change to happen, as well as its implications and limitations. © Common Ground Research Networks, Cristóbal Moreno Muñoz, Vader Johnson, Lucía Sánchez de la Guía, All Rights Reserved.